Search for squarks and gluinos in events with isolated leptons, jets and missing transverse momentum at √s = 8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
The results of a search for supersymmetry in final states containing at least one isolated lepton (electron or muon), jets and large missing transverse momentum with the ATLAS detector at the Large Hadron Collider are reported. The search is based on proton-proton collision data at a centre-of-mass energy √s = 8TeV collected in 2012, corresponding to an integrated luminosity of 20 fb−1. No significant excess above the Standard Model expectation is observed. Limits are set on supersymmetric particle masses for various supersymmetric models. Depending on the model, the search excludes gluino masses up to 1.32TeV and squark masses up to 840 GeV. Limits are also set on the parameters of a minimal universal extra dimension model, excluding a compactification radius of 1/Rc = 950 GeV for a cut-off scale times radius (ΛRc) of approximately 30.